2015
DOI: 10.1186/s40066-015-0048-y
|View full text |Cite
|
Sign up to set email alerts
|

Rural women’s farmers access to productive resources: the moderating effect of culture among Nupe and Yoruba in Nigeria

Abstract: Background: This paper analyzes ownership and control of productive resources by gender as determined by culture. This is premised on the fact that past researchers have isolated gender and productive resources on one hand and gender and culture on the other. In this paper, the novelty is the exploration of the interplay among culture, gender and productive resources. Using a descriptive quantitative research design, a simple random sampling was used to select 100 households from a sampling frame of 200 househ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…The study by Ajadi et al (2015) affirms such gender disparities by demonstrating how the interplay of gender, ownership and decision-making including culture exert a significant influence on women's access and control of productive resources among the Nupe and Yoruba women in Nigeria.…”
Section: Selected Demographicsmentioning
confidence: 84%
“…The study by Ajadi et al (2015) affirms such gender disparities by demonstrating how the interplay of gender, ownership and decision-making including culture exert a significant influence on women's access and control of productive resources among the Nupe and Yoruba women in Nigeria.…”
Section: Selected Demographicsmentioning
confidence: 84%
“…2 Their geographical proximity to the Yoruba, the second largest ethnic group in Nigeria, has led to many cross-cultural influences. Living arrangements among Nupe and Yoruba people in northern Kwara state are comparable, based on patrilineal and patrilocal family structures in which polygyny is common (Ajadi et al 2015).…”
Section: A Participant Sample and Study Contextmentioning
confidence: 99%
“…The number of wives a man has is an indicator of wealth and status (Nadel 1942). Both deuterogamy (i.e., marrying the wife of a deceased brother) (Ajadi et al 2015) and divorce are common in Nupe culture (Katcha 1978).…”
Section: A Participant Sample and Study Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, even when women own the land, they tend to have limited access to financing, quality inputs, extension services and knowledge of agricultural practices. Ajadi et al (2015), Soyemi (2014), Adeyemo et al (2015), and Koyenikan and Ikharea (2014) found that women had less access to agricultural resources and information on agricultural technologies. Beuchelt and Badstue (2013) in a study emphasized that the reduction of gender disparities and the empowerment of women leads to better food and nutrition security for households and significantly strengthens other development outcomes such as child education.…”
Section: Introductionmentioning
confidence: 99%